Impacts of environmental conservation programs on regional economic structural change in Guizhou, China, from 2002 to 2012: An input-output analysis - Shuning Chen; Masaru Kagatsume (Journal of Economic Structures, 2018)
In 1999, the Grain to Green Program (GTGP) was initiated in China as payment of ecosystem service and the largest land conservation program. This paper evaluates the impact of this conservation program on the regional economic structural change in Guizhou Province. We generate the agriculture-based regional input-output tables of 2002, 2007 and 2012. The production and employment inducements are calculated by using the Leontief inverse matrix. The key sectors are figured out by applying the linkage analysis. The RAS analysis is used for categorizing sectors as the potentially growing or shrinking industry. The results indicate the undesired effect of the GTGP and the EMP on the upstream supplier and downstream industries for agricultural production. Rural household expenditure was changed by the subsidies and shows negative effect on agricultural production. In the second stage of policy implementation, we found the depression of rural economies. The shrinking potential of the rural sector forced the further cutback of these upstream and downstream industries. The surplus rural labors find difficulties in searching for jobs in the local labor market and should move out of this region. From these results, we suggest the local government should reconsider the economic influence of the GTGP and EMP rather than emphasize the environmental issues and intend to improve rural welfare.
Keywords: 330; Payment for ecosystem services (PES); Guizhou Province; RAS analysis; Agriculture-based IO tables; Net forward and backward linkage